Changing Fortunes during Economic Transition - Low-Wage Persistence before and after German Unification - Andre Nolte; Nicole Gürtzgen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper studies whether the transition from a centrally planned to a market economy offers fundamentally new perspectives for those who, in economic terms, were relatively deprived under the old regime. Previous empirical research on this question has been limited by the availability of suitable representative longitudinal micro-data that tracks individuals' labour market careers across different political and economic regimes. Our study seeks to fill this research gap by looking at the transition of Eastern Germany following German Unification. Using a unique large-scale German administrative data set, we measure individuals' relative economic position by exploiting information on whether individuals were in the bottom of the pre-unification wage distribution. We further approach the question of how workers' low or high-wage status determines their wage and labour market status within and across different regimes. We first demonstrate that unobserved factors are the main drivers of low-wage persistence and are regime-dependent. We further show that, consistent with signalling considerations, economic dependencies across different regimes are only of minor relevance. Genuine state dependence after Unification amounts to relatively large values of about 15 per cent for males and 19 per cent for females. This measure of persistence is heterogeneous across time, indicating a strong adjustment process and the importance of signalling considerations.
Keywords: J31; J64; P21; 330